PENINGKATAN KETERAMPILAN GULING BELAKANG DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN BERBASIS ANIMASI DI SD NEGERI 3 SUNGAPAN KULON PROGO - Sayekti, Khusnul Aswin; Pratyas, Rinda; Pamuji, Juni Teguh (Pelita - Jurnal Penelitian Mahasiswa UNY, 2012)
The research is aimed at improving the teaching of back rolling by using animation basedteaching media in grade four of SD Negeri sungapan 3 Kulon Progo.This research was a classroom action research. It was conducted in three meetings andeach meeting showed the stages of the development process of back rolling in the physicaleducation. The subjects of the research were the grade four students of SD Negeri Sungapan3 in the second semester of the 2011/2012 academic year. The instruments used to collectdata were observation sheets, questionnaires, and tests. The data were analiyseddescriptively.The reserach result showed that the animation based teaching media in the teachingand learning process of back rolling could improve the students’ spirit, enthusiasm, funatmosphere, and their marks.Keywords: media, animation, back rolling